The Story of Bantugan. [anthology].
This is a legend of the Mohammedan tribes or Moros of Mindanao. It deals with the adventures of Bantugan and of his friend Datto Baningan.
Found in: Philippine Folk Literature : The Epics. (GR 325 P48 2001 v.8)
Keywords: Literature-Collections.